2020
DOI: 10.4018/ijeei.2020070105
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Social Media in Facilitating Women Entrepreneurs in India

Abstract: This article explores the role of social media in facilitating women entrepreneurs in India. It adopts a case study approach to explore the effectiveness of social media platforms in supporting women entrepreneurs. PULA (Pune Ladies), a closed Facebook Group, set up in 2015 for women in Pune, was selected as a case study. Fifteen in-depth interviews were conducted among 15 active women entrepreneurs of this group to explore the benefits received in terms of visibility, marketing opportunities, revenue generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Eentrepreneurship, in this context, helps women to effectively balance their work and family which serves to reduce workplace burnout and familial stress in addition to increasing economic resources. A lot of studies have also pointed out that women entrepreneurs are more focused on pursuing social than economic goals that not just empower women but also result in the empowerment of the regional community (Bedarkar, 2020). Various studies have shown that a difference in motivation exists between men and women concerning entrepreneurship as men are more likely to choose employment that fosters promotion, attractive payment, and security whereas women are likely to choose entrepreneurial careers that emphasizes flexible hours and freedom of initiative (Zou, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Eentrepreneurship, in this context, helps women to effectively balance their work and family which serves to reduce workplace burnout and familial stress in addition to increasing economic resources. A lot of studies have also pointed out that women entrepreneurs are more focused on pursuing social than economic goals that not just empower women but also result in the empowerment of the regional community (Bedarkar, 2020). Various studies have shown that a difference in motivation exists between men and women concerning entrepreneurship as men are more likely to choose employment that fosters promotion, attractive payment, and security whereas women are likely to choose entrepreneurial careers that emphasizes flexible hours and freedom of initiative (Zou, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While these challenges may seem daunting, they also provide fertile ground for innovation and differentiation. SMEs that can navigate and adapt to these distinctive market conditions stand to gain a competitive edge and realize substantial growth potential (Mishra, M. 2020, Bedarkar, M et al, 2020). SME Internationalization in Emerging Markets -According to Coviello and Munro (1995), SMEs internationalize for a variety of reasons, including market, resource, and efficiency-related goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a narrow sense, it relates to the internationalization decision of a brand name, logo, and personality. Factors affecting domestic consumers' purchase intention include quality perception, credibility, country of origin, and brand familiarity (Bedarkar et al, 2020). The potential substitution relationship among these factors reflects that emerging market enterprises should choose a targeted driving path to implement brand internationalization strategies.…”
Section: Literature Reviewmentioning
confidence: 99%